New Advances in Marine Engineering Geology - Yang, Qing; Jeng, Dong-Sheng; Liu, Xiaolei; Wang, Yin; Sturm, Hendrik (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The ocean is the cradle of life and is rich in natural resources. With the worldwide boom in exploration and application of ocean resources, a dramatically increasing amount of coastal engineering and offshore engineering facilities have been constructed in the last few decades. The rapid development of human economic activities and the global climate change have significant impacts on the marine environment, resulting in frequent geological disasters. Under this circumstance, there is an urgent demand for a platform for scientists and engineers to share their state-of-art research outcomes in the field of Marine Engineering Geology. This book is a collection of a series of articles from the 2nd International Symposium of Marine Engineering Geology (ISMEG 2019), presenting some of the recent efforts made towards marine engineering geology and geotechnics, including theoretical advances, laboratory and field testing, design methods, and the potential for further development of these disciplines.